Activation of STING in the pancreatic tumor microenvironment: A novel therapeutic opportunity. (10th July 2022) - Chamma, Hanane; Vila, Isabelle K.; Taffoni, Clara; Turtoi, Andrei; Laguette, Nadine
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a cancer of poor prognosis that presents with a dense desmoplastic stroma that contributes to therapeutic failure. PDAC patients are mostly unresponsive to immunotherapy. However, hopes to elicit response to immunotherapy have emerged with novel strategies targeting the Stimulator of Interferon Genes (STING) protein, which is a major regulator of tumor-associated inflammation. Combination of STING agonists with conventional immunotherapy approaches has proven to potentiate therapeutic benefits in several cancers. However, recent data underscore that the output of STING activation varies depending on the cellular and tissue context. This suggests that tumor heterogeneity, and in particular the heterogeneity of the tumor microenvironment (TME), is a key factor determining whether STING activation would bear benefits for patients. In this review, we discuss the potential benefits of STING activation in PDAC. To this aim, we describe the major components of the PDAC TME, and the expected consequences of STING activation. Highlights: The tumor microenvironment (TME) of pancreatic ductal adenocarcinoma is heterogenous. The TME comprises both immune and non-immune cells. STING activation bears pro- or anti-tumor effects depending on the cellular types. The impact of STING agonists in non-immune cells requires further investigation.